Implikasi manajerial nilai tambah produk susu pasteurisasi, susu sterilisasi & keju mozzarella PT. Greenfields indonesia terhadap volume produksi (production volume & production value) - Irawati, Yeyen; Hidayat, Nur; Sucipto, Sucipto (Jurnal Sains Peternakan, 2019)
Research is dedicated to obtain product value added of Greenfields Indonesia’s pasteurized milk, sterilized milk & Mozzarella cheese, using Hayami Methods modification deals with Gross Profit Margin (GPM) variable, according to internal corporate perspectives (process perspectives) involving filling & packing machines efficiency, final product defect & yield percentage and external corporate perspectives (market perspectives) involving final product price also figure out it’s managerial implication to corporation’s production both in production volume & production value as consequence of the corporation policy increasing in amount of 600 Fressian Holstein cows to Corporation Dairy Farm (2015). Process perspectives & market perspectives product value added (production volume & production value) ‘Greenfields’ plain milk 1000 ml pasteurized milk (2011, GPM 44,921%) 366795,498 litre/period (5,046% ) 9.794.193 Rp/period (17.058 Rp/pack/period), ‘Greenfields’ & ‘Fresh & Natural’ plain milk 1000 ml sterilized milk (2014, GPM 63,885%) 1211007,197 litre/period (5,247%) 22.862.834.354  Rp/period (8.481 Rp/pack/period), ‘Real Good’ flavoured milk 180 ml sterilized milk (2014, GPM 63,885%) 70288,463 litre/period (0,357%) 1.048.973 Rp/period (1.207 Rp/pack/period) and ‘Greenfields’ 1000gr; 330gr; 300gr; 250gr; 200gr Mozzarella cheese (2014, GPM 63,885%) 2181,114 litre/period (0,0265%) 240.053.832 Rp/period (4.241 Rp/Mozzarella pack/period) 289.157.056 Rp/period (5.115 Rp/Shredded Mozzarella pack/period). Product value added managerial implication (production volume & production value) (2016, GPM 44,158%) shows that pasteurized milk & sterilized milk both at 108,564% level of change in production volume & constant level in production value and Mozzarella cheese at 108,215% - 108,738% level of change in production volume & 226,200% - 226,585% significant level of change in production value. The percentage value also represents percentage value of raw milk procurement of Greenfields Indonesia’s Corporation Dairy Farm